Association between Patient Portal use and Office Visits. - Silver, Reginald A.; Subramaniam, Chandrasekar; Stylianou, Antonis (Journal of Medical Systems, 2021)
Extant research on the relationship between portal use and office visits is mixed. Some researchers have stated that there is no correlation between the two events, others have found a positive correlation, and still others have found a negative correlation between portal use and office visits. Through the use of system-generated data from two different portal systems, we demonstrate the correlation between portal visits and office visits. We also demonstrate how this correlation differs between two institutions and across three demographic attributes. We performed a retrospective bivariate correlation analysis between portal visits and office visits. The correlation analysis was followed by an application of Fisher's z transformation of the correlation coefficients to determine significant differences in correlation across ethnicity, gender, and age. We found a positive and statistically significant correlation between portal visits and office visits among both hospital patients (n = 2,594, r =.239, p <.000) and university health service patients (n = 1,233, r =.596, p <.000). This correlation varies significantly across the dimensions of ethnicity, gender, and age. Our findings support the importance of portal use in the care continuum. Future research should aim to better understand the nuance of personal characteristics on the relationship between portal visits and office visits. Knowing these nuances can assist practitioners with further promoting patient self-engagement through portal use.